J(x) = x^2 – 2x + 5 and

k(x) = 4x^2 – 3

j(-4) – k(5)

Skip to content# J(x) = x^2 – 2x + 5 andk(x) = 4x^2 – 3j(-4) – k(5)

Mathematics ##
Comments (3) on “J(x) = x^2 – 2x + 5 andk(x) = 4x^2 – 3j(-4) – k(5)”

### Leave a Reply Cancel reply

J(x) = x^2 – 2x + 5 and

k(x) = 4x^2 – 3

j(-4) – k(5)

The answer would be: b

[tex]Which is true about the functional relationship shown in the graph? pls me[/tex]

the answer is C.

Step-by-step explanation:

b) 1/3 * 1/5

step-by-step explanation:

each smallest part is 1/15 since the written one is 1/5 and it's divided by 3 equal parts. (1/5 )/3 = 1/15 = 1/3 * 1/5

[tex]Which product is shown on this number line[/tex]